Many-body effects in semiconducting single-wall silicon nanotubes - Wei, Wei; Jacob, Timo (Beilstein Journal of Nanotechnology, 2014)
The electronic and optical properties of semiconducting silicon nanotubes (SiNTs) are studied by means of the many-body Green’s function method, i.e., GW approximation and Bethe–Salpeter equation. In these studied structures, i.e., (4,4), (6,6) and (10,0) SiNTs, self-energy effects are enhanced giving rise to large quasi-particle (QP) band gaps due to the confinement effect. The strong electron−electron (e−e) correlations broaden the band gaps of the studied SiNTs from 0.65, 0.28 and 0.05 eV at DFT level to 1.9, 1.22 and 0.79 eV at GW level. The Coulomb electron−hole (e−h) interactions significantly modify optical absorption properties obtained at noninteracting-particle level with the formation of bound excitons with considerable binding energies (of the order of 1 eV) assigned: the binding energies of the armchair (4,4), (6,6) and zigzag (10,0) SiNTs are 0.92, 1.1 and 0.6 eV, respectively. Results in this work are useful for understanding the physics and applications in silicon-based nanoscale device components.
Keywords: Bethe–Salpeter equation; excitons; GW approximation; many body effects; silicon